Korelasi Health Belief dengan Kepatuhan Pembatasan Cairan dan Garam pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Murni Teguh Medan - Kalvin Ginting; Sutomo Kasiman; Cholina Trisa Siregar (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
know that they suffer from a disease, they will take more serious care for their health and take medication in accordance with doctors’ recommendation. However, there are still many patients with CKD do not comply with the doctors’ recommendation. Health belief is the belief adhered in undergoing medication will affect the believers’ health. The objective of this research was to analyze the correlation of health belief with fluid and salt restriction compliance in patients with CKD undergoing hemodialysis. This research employed quantitative design with cross sectional method. There were 150 patients with CKD undergoing hemodialysis in total that were taken as the samples. This research was conducted at Murni Teguh Hospital, Medan. The samples were selected by applying total accidental technique. The data were collected through questionnaires, and the analysis was made by using Pearson test. The results of Pearson test on the correlation of health belief with patients’ fluid and salt restriction compliance demonstrated value of p = 0.000. It indicated that health belief are correlated with the fluid and salt restriction compliance of patients with CKD undergoing hemodialysis. It is recommended that nurses improve their education quality and frequency by paying attention to patients.